Reproductive toxicology and clastogenic evaluation in mice of a phytotherapeutic formulation obtained from Cinchona calisaya Weddel (Rubiaceae) used in Brazilian folk medicine as female fertility stimulant - Langaro do Amaral, Vera Lucia; Frajbat, Marcel; Petreanu, Marcel; Zermiani, Tailyn; Freitas, Rilton Alves de; Maistro, Edson Luis [UNESP]; Niero, Rivaldo; Belle Bresolin, Tania Mari; Cechinel Filho, Valdir; Andrade, Sergio Faloni de (Elsevier B.V., 2014)
Ethnopharmacological relevance: In Brazil, a phytotherapeutic preparation produced from a standardized tincture of Cinchona calisaya Weddel such that each mL of product contains 400 mu g of quinine, known in Portuguese as Agua Inglesa (R) (English water), is indicated by the manufacturer as a tonic, appetite stimulant, and digestive. However, this preparation has long been used in folk medicine as a female fertility stimulant. Despite its widespread use in folk medicine to stimulate female fertility, no study has been undertaken to assess the potential teratogenic and genotoxic effects of this phytotherapeutic preparation. The aim of the present study was to investigate possible toxic reproductive effects in mice caused by exposure to Agua Inglesa (R), either before mating or during the pre- and post-embryo implantation periods. The genotoxic potential was evaluated using the micronucleus assay.Material, Methods, and Results: Virgin female mice, with at least one estrous cycle evidenced by vaginal cytology, were divided into five groups of 15 individuals each (Group I - control, Group II - treated with ethanol solution at 16%, Groups III, IV and V treated with phytotherapeutic preparation at 1.5 mL/kg/day, 3.0 mL/kg/day and 4.5 mL/kg/day, respectively). After the first 28 days of treatment, females were caged individually with adult fertile males. Pregnant females continued to receive treatment for seven days (preimplantation period). Body weight was recorded weekly during treatment. Signs of toxicity (weight loss, food intake, piloerection, apathy, prostration, diarrhea, seizures, behavioral changes, and locomotion) were also observed. The females were sacrificed on the 15th day of pregnancy, uterine horns were evaluated for implantation, and the placental index was recorded. In the micronucleus test, 2000 polychromatic erythrocytes (PCE) per animal, obtained from bone marrow, were scored. Results The results showed that exposure of the females during the pre- and post-implantation periods did not significantly alter the reproductive capacity (p < 0.05); however, in higher dose (three times human dose)reduction of fetal weight was observed. There was no difference between the control and phytotherapeutic preparation (p > 0.05) in terms of the average number of micronucleated polychromatic erythrocytes.Conclusions: Although folk medicine suggests that the Agua Inglesa (R) preparation is useful as a female fertility stimulant, no such effect was confirmed in mice. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Agua Inglesa (R); Micronucleus; Reproductive toxicology